Analisis Tindakan Perawatan Yang Dilakukan pada Pasien Dengan Phlebitis di RSUD PROF DR. Margono Soekardjo Purwokerto - Handoyo,; Triyanto, Endang (Jurnal Keperawatan Soedirman, 2007)
Intravenous therapy is commonly used to treat patients and it is received through a peripheral cannula by most hospitalized patients. A consequence of intravenous (IV) devices is that risk of nosocomial infection is increased, particularly septicemia. Inflammation, hard vein and thrombophlebitis, and local tenderness are common complication of IV therapy. This can lead to enhanced morbidity and mortality rates. Some treatments to cure phlebitis patients have been done to eradicate phlebitis patients during hospital stay. However, mostly phlebitis treatments have not been standardized as procedure at hospital. Therefore, this study will analyse nurses’ treatment when they are performing phlebitis patient care that mostly done at Margono Soekardjo Hospital. The purpose of the study was to analyse nurses’ treatment when caring phlebitis patients that mostly were done at medical and surgical ward Margono Soekardjo Hospital of Purwokerto This study utilized survey. Of 38 nurses at Teratai and Asoka wards at Margono Soekardjo Hospital were involved in this study. Respondents were chosen by quaote sampling method. Criteria of respondents were nurses at surgical ward who have graduated from DIII nursing with 1 year experience in clinical setting The study show that nurses tend to elevated phlebitis area to cure phlebitis as the first choice at (26%), furthermore, by warm compress and range of motion of the area of phlebitis have the second and the third rank at (23%) and (18%) respectively